Mitigation of Occupational Hazards in Chemical Handling for Homecare Production Using a Programmable Logic Controller Control System Approach - Nor Edyra Sofea Nor Suzaidee; Amir Haziq Abdul Razak; Asmidi Farhan Mashan (Progress in Engineering Application and Technology, 2026)
This study addresses critical occupational hazards associated with manual sodium hydroxide (NaOH) handling at a homecare production plant in Petaling Jaya, Selangor, where current semi-manual processes exceed human capacity for safety. Existing reliance on Personal Protective Equipment (PPE) fails to comply with Malaysia’s OSHA 1994 and USECHH Regulations 2000; therefore, this research aims to design and validate a sequential PLC-based control system to automate caustic transfer. Using an Applied Engineering and Simulation Design methodology, an eleven-rung logic program was developed featuring a state-based logic approach and dual-latch structure to ensure discrete machine cycles. Software-in-the-Loop (SIL) validation confirmed the system provides a consistent 20-second dosage cycle using high-precision Timer-On-Delay (TON) instructions. Results demonstrate that the safety logic, including a Master Emergency Stop, achieves near-instantaneous de-energization, successfully eliminating manual variability and accidental re-triggering. The study concludes that PLC-based engineering controls are a superior alternative to administrative measures, providing a viable template for high-risk automation retrofitting in the Malaysian manufacturing industry.